Does the 'equal management of equal risks' model cause overtreatment in patients with positive cervical cytology results for ASCUS/non‐HPV16/18 oncogenic types?. Issue 2 (16th November 2018) - Karaca, İbrahim; Öztürk, Mustafa; Comba, Cihan; Demirayak, Gökhan; Erdoğan, Şakir Vokan; Hoşgören, Murat; Özdemir, İsa Aykut
Abstract : Objectives: According to the American Society of Colposcopy and Cervical Pathology (ASCCP), cervical cytology patients who test positive for atypical squamous cells of undetermined significance (ASCUS) and the human papilloma virus (HPV) positive are recommended to undergo colposcopies. This study compared the colposcopic biopsy evaluation results of patients with positive cervical cytology results for ASCUS and HPV with regards to their HPV genotypes. Methods: This study included 179 patients who underwent cervical cancer screening tests between June 2015 and June 2017 and whose results displayed positive cervical cervical cytology results for ASCUS and HPV. Cytological samples were classified using the Bethesda system in liquid‐based specimens. The Hybrid Capture II system was used to define the HPV‐DNA. Colposcopic diagnoses and biopsy results were compared in terms of the outcomes of the Pap test and HPV genotypes. Results: There were 107 ASCUS/HPV16/18‐positive patients. Of the HPV 16/18 positive patients; 28 (26.1%) patients were detected with CIN1, 8 (7.5%) patients were detected with CIN2, 6 (6%) patients were detected with CIN3, and 1 (0.9%) patient was detected with cervical cancer. Of the 72 non‐HPV 16‐18 positive patients; 8 (11%) patients were detected with CIN1 and 2 (2.7%) patients were detected with CIN2. Conclusion: This study believes that the ASCCP recommendations, which state that a 'colposcopy should be performed on all women with positive cytology for ASCUS/non‐HPV16/18 oncogenic types', is required to be revised. This will reduce the rate of the colposcopy procedures by 40% in women with ASCUS/HPV positivity.